Comparative study of knowledge, attitude, and practices towards COVID-19 among MBBS Prof 1 students of two successive years in Motilal Nehru Medical College, Prayagraj, Uttar Pradesh - Singh, Richa; Beenu; Dwivedi, Garima (International Journal Of Community Medicine And Public Health, 2023)
Background: Coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by a novel coronavirus. Three waves of COVID 19 have hit us so far. With repeated waves of any disease, it has been observed that panic in the community and healthcare personnel decreases and knowledge and attitude towards the disease and diseased improves. Keeping this in mind, the following study was conducted with the following objective. Aim of this study was to assess and compare knowledge, Attitude and Practices of students of MBBS phase I of two consecutive years- 2020 batch and 2021 batch regarding COVID-19. Methods: Data was collected from two successive MBBS first professional batch students by using questionnaire and assessment of knowledge, attitude and practice was done on the basis of scoring system described by Kaliyaperumal. Results: It was observed that among phase I MBBS students (2020 batch) majority i.e. 55.89% were having medium level of knowledge, with a range of score 11‐15. While among phase I MBBS students (2021 batch), majority i.e. 62.82% were having high knowledge score in the range of 16-21. Regarding the attitude scores, majority of students in both the batches (52.82% in phase I (2020 batch) and 65.45% in phase I (2021 batch)) were having good attitude (score >6). Practice scores were mostly satisfactory (score 3-5) among both batches’ MBBS students. Conclusions: The study revealed that the attitude among students was good while knowledge and practice were satisfactory.